How much power do oppositions have? Comparing the opportunity structures of parliamentary oppositions in 21 democracies. Issue 1 (2nd January 2017) - Garritzmann, Julian L.
ABSTRACT: A political system cannot be imagined without opposition. Despite this crucial position in politics, political science has largely neglected to study oppositions. Attempting to fill this gap, this article analyses the institutional opportunities of parliamentary oppositions. It offers a parsimonious framework by distinguishing two dimensions of opposition influence: some institutions enable oppositions to control governments, while others offer opportunities to present alternatives. A comparison of oppositions' opportunities in 21 democracies shows that countries fall into four groups along these dimensions: in majoritarian democracies, weak control mechanisms are countered by excellent opportunities to publicise alternatives. Consociational democracies are characterised by strong control mechanisms, but provide only weak opportunities to present alternatives. Moreover, in Southern Europe, control mechanisms and opportunities to present alternatives are weak, while both are pronounced in Nordic Europe. The results are summarised in three indices that can easily be applied in future research examining oppositions and their power.